A Novel International Partnership for Actionable Evidence on Urban Health in Latin America: LAC‐Urban Health and SALURBAL. Issue 4 (19th June 2018) - Diez Roux, Ana V.; Slesinski, S. Claire; Alazraqui, Marcio; Caiaffa, Waleska Teixeira; Frenz, Patricia; Jordán Fuchs, Ricardo; Miranda, J. Jaime; Rodriguez, Daniel A.; Dueñas, Olga L. Sarmiento; Siri, José; Vergara, Alejandra Vives
Abstract: This article describes the origins and characteristics of an interdisciplinary multinational collaboration aimed at promoting and disseminating actionable evidence on the drivers of health in cities in Latin America and the Caribbean: The Network for Urban Health in Latin America and the Caribbean and the Wellcome Trust funded SALURBAL (Salud Urbana en América Latina, or Urban Health in Latin America) Project. Both initiatives have the goals of supporting urban policies that promote health and health equity in cities of the region while at the same time generating generalizable knowledge for urban areas across the globe. The processes, challenges, as well as the lessons learned to date in launching and implementing these collaborations, are described. By leveraging the unique features of the Latin American region (one of the most urbanized areas of the world with some of the most innovative urban policies), the aim is to produce generalizable knowledge about the links between urbanization, health, and environments and to identify effective ways to organize, design, and govern cities to improve health, reduce health inequalities, and maximize environmental sustainability in cities all over the world. Abstract : This article describes an ongoing global interdisciplinary collaboration that works to understand health in Latin American and Caribbean cities through research that can inform urban policies that improve health, health equity, and sustainability. The processes, challenges, and lessons learned to date in launching and implementing these collaborations are addressed.